The questions of objectivity in news related to "7/7" in the British press - Miklós Anna; Kocsik András (2007)
This thesis examines the approaches of 6 highlighted British newspapers in connection with the news published by them after the 2005 London terror attacks. The analysis includes The Times, The Independent, The Daily Telegraph, The Guardian, The Daily Mirror and The Sun newspapers. I will demonstrate that from these papers only The Independent has provided the most objective approach to publishing news related to "7/7", and the other newspapers have issued news that have been highly influenced by the papers' subjective approaches.
Keywords: Pedagógusképzés